Mobility of sub-Saharan Africa doctoral graduates from South African universities—A tracer study. (July 2019) - Kahn, Michael; Gamedze, Thandi; Oghenetega, Joshua
Highlights: The study determines that 77% of foreign African graduates return home ; only 7% leave the continent. South African higher education is not a direct contributor to African brain drain of scarce PhD holders. The study breaks new ground using social media and doctoral repositories to track and trace the graduate students. Abstract: This article reports on a novel approach to tracing the career paths of recent doctoral graduates from South African universities. Little was previously known regarding the mobility of students from sub-Saharan Africa who obtain their doctoral degrees in South Africa's universities, despite this group comprising over a third of South Africa's total doctoral graduates. Given South Africa's high-level skills shortage, and the fact such students are subsidized by the South African taxpayer, their career trajectory on completion is of interest to policy. A tracer study styled as MOTHS – Mobility of the Highly Skilled - used unconventional techniques to track the career paths of graduates over 2012 to 2013. Results of the first phase of the project indicate 'brain circulation' whereby the majority of graduates return to their country of origin. Implications for higher education and immigration policy are discussed.